Bar wars contesting the night in contemporary British cities - Hadfield, Phil. (Oxford : Oxford University Press, 2006)
Located within a long tradition of urban ethnography, this book offers analyses of social control in bars and clubs, courtroom battles between local communities and the drinks industry, and street-level policing. It is useful for those wishing to understand the governance of crime and social order in contemporary cities.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Drinking of alcoholic beverages -- Government policy -- Great Britain; Binge drinking -- Social aspects -- Great Britain; Social control -- Great Britain; Sociology, Urban -- Great Britain